1998
DOI: 10.1063/1.367426
|View full text |Cite
|
Sign up to set email alerts
|

Local order of polymer derived amorphous SixCyNz

Abstract: Analysis of geometrical effects on the behavior of transverse and longitudinal modes of amorphous silicon compoundsWe report on the local order of a-Si 39 C 61 , a-Si 40 C 24 N 36 , and a-Si 26 C 40 N 34 . The total structure factors and pair correlation functions obtained by x-ray diffraction as well as the coordination numbers of the first coordination sphere are presented. All materials exhibit a distinct short range order. In the case of a-Si 39 C 61 , a stoichiometric amorphous SiC phase besides an amorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the case of glasses, an increase in RE coordination with the anions can result in an increase in the fraction of nonbridging anions. Studies of SiAlRE oxynitride glasses revealed that the average coordination number for La with oxygen was 8.8 [30]. Additional studies of the SiAlRE oxide glasses have also shown that the coordination number of oxygen with Y is $6.6, which increased for La [31].…”
Section: Thermal Expansionmentioning
confidence: 92%
“…In the case of glasses, an increase in RE coordination with the anions can result in an increase in the fraction of nonbridging anions. Studies of SiAlRE oxynitride glasses revealed that the average coordination number for La with oxygen was 8.8 [30]. Additional studies of the SiAlRE oxide glasses have also shown that the coordination number of oxygen with Y is $6.6, which increased for La [31].…”
Section: Thermal Expansionmentioning
confidence: 92%
“…[1][2][3] Owing to the strong covalent bonding and structural amorphous nature of PDCs, the ceramics in the ternary system Si-C-N as well as quaternary ceramics Si-M-C-N(O) (M = B, Al, Zr) have excellent structural stability, near-zero steady state creep as well as oxidation and corrosion resistance at high temperatures (1500 • C). 1,[4][5][6][7] Recently, numerous studies of SiCN ceramics have been reported on their amorphous structure and their high-temperature evolution over the ranges of micro to nano-scales. For understanding of the unusual stability of PDCs at high-temperatures, a wide variety of experimental techniques have been implemented such as X-ray and neutron diffractions, 2-5 transmission electron microscopy 6 and nuclear magnetic resonance.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, the changes in the amorphous network structure (usually referred to as medium-range order) during nitridation of silica have not been fully clarified, although there are several studies on the characterization of Si-(O)-N, Si-(O)-C and Si-(O)-C-N system derived from organic precursors. [12][13][14][15][16][17][18][19][20][21] Although local structures may be determined by NMR or EXAFS techniques, the structural information obtained by these methods is not sufficient to determine the nature of the ring-structures in the medium-range order. Diffraction methods (either X-ray or neutron) are commonly used to obtain the atomic arrangement of disordered materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chino and Okubo have investigated the detailed transformation process from mesoporous silica to mesoporous silicon oxynitride, and clarified the role of surface defect species during nitridation 6 . However, the changes in the amorphous network structure (usually referred to as medium‐range order) during nitridation of silica have not been fully clarified, although there are several studies on the characterization of Si–(O)–N, Si–(O)–C and Si–(O)–C–N system derived from organic precursors 12–21 …”
Section: Introductionmentioning
confidence: 99%